2018
DOI: 10.1002/ldr.3116
|View full text |Cite
|
Sign up to set email alerts
|

Human‐induced land degradation and biodiversity of Classical Karst landscape: On the example of enclosed karst depressions (dolines)

Abstract: In the karst landscape of the Kras Plateau (south‐west Slovenia), we studied the impact of historical human‐induced land degradation on biodiversity by studying the characteristics and changes in vegetation of degraded and nondegraded karst depressions (dolines). Intensive human‐induced land degradation began as a consequence of the abandonment of traditional land use; thus, many dolines have disappeared by being completely filled with waste material and overgrowth. The study is based on a chronosequence appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…Generally, disturbances reduced the number of species that are cool-adapted, moist-adapted and of high conservation importance, reducing the conservation value of dolines. Several other studies have highlighted that climatically diverse habitats are extremely sensitive to anthropogenic disturbances and that their recovery from such disturbances may be slow or incomplete (Stylinski and Allen 1999;Lindenmayer et al 2017;Breg Valjavec et al 2018b). We found that stronger disturbances that have a significant effect on the vegetation structure, such as intensive logging and invasion by Calamagrostis epigejos, can lead to significant declines of cool-adapted, moist-adapted and high-conservation importance plant species in dolines (Figs.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Generally, disturbances reduced the number of species that are cool-adapted, moist-adapted and of high conservation importance, reducing the conservation value of dolines. Several other studies have highlighted that climatically diverse habitats are extremely sensitive to anthropogenic disturbances and that their recovery from such disturbances may be slow or incomplete (Stylinski and Allen 1999;Lindenmayer et al 2017;Breg Valjavec et al 2018b). We found that stronger disturbances that have a significant effect on the vegetation structure, such as intensive logging and invasion by Calamagrostis epigejos, can lead to significant declines of cool-adapted, moist-adapted and high-conservation importance plant species in dolines (Figs.…”
Section: Discussionmentioning
confidence: 54%
“…Dolines and their unique biota are particularly vulnerable to anthropogenic disturbances (De Waele 2009;Breg Valjavec et al 2018b;Jian et al 2018). For instance, road construction, overgrazing and nutrient addition by sheep have seriously threatened plants endemic to dolines in the Greek Archipelago biodiversity hotspot (Egli 1991;Brullo and Giusso del Galdo 2001;Iatroú and Fournaraki 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, by themselves, human impact indicators cannot highlight the mechanisms of environmental change. For example, Breg Valjavec et al (2018b) found that hemeroby indicators were suitable to infer the degradation of Slovenian karst depressions resulting from landfilling. The same authors characterized the same areas by applying moisture, nutrient, and pH Ellenberg indicators (Breg Valjavec et al, 2018a), which provided insight into edaphic effects of landfilling.…”
Section: Discussionmentioning
confidence: 99%
“…Sites with higher hemeroby values have distinct, degraded communities of non‐native and weedy (i.e. ruderal) species (Breg Valjavec et al, 2018b). The vegetation of sites in lower hemeroby categories is characteristic of late‐successional communities, some of which can be indicative of past European landscapes (Sukopp, 1969; cf.…”
Section: Introductions To the Human Impact Indicator Systemsmentioning
confidence: 99%
“…Historic soil contamination within floodplains is essential to consider as related to water resource planning and the construction of large hydraulic infrastructure, such as dams and reservoirs. Breg Valjavec, Zorn, and Čarni (2019) consider this topic in relation to dam and reservoir planning for the Sava River (Slovenia). Their study concerns problems of floodplain gravel pits infilled with polluted waste and the potential for increased groundwater flow because of dam impoundment.…”
Section: Historic Human Impacts On Modern Environmental Processes Andmentioning
confidence: 99%